Effect of light intensity on leaf scorching in nursery seedlings of cardamom (Elettaria cardamomum Maton) - KULANDAIVELU, K C RAVINDRAN, G (Journal of Spices and Aromatic Crops, 2017)
Studies on leaf scorching in nursery seedlings of cardamom (Elettaria cardamomum) grown at Thadiyankudisai (Tamil Nadu, India) indicated that total biomass, chlorophyll and protein contents, and photochemical activities were adversely affected in leaf scorched seedlings grown under full light (100% of total sunlight), when compared to healthy seedlings grown under medium light (45-55% of total sunlight).